The Dynamics of Nationalism and Global Citizenship in the Development of the Pancasila Campus Tourism Model - Tarsidi, Deni Zein (CV. Rayyan Dwi Bharata, 2025)
Experiential civic education models rooted in symbolic spaces within university campuses have rarely been systematically examined, despite their significant potential to bridge national values and global consciousness. This study aims to construct an educational tourism model at the Pancasila Fortress Campus (Kampus Benteng Pancasila) of Universitas Sebelas Maret as a site for dialectical engagement between nationalism and global citizenship. Employing a qualitative phenomenological approach, data were collected through in-depth interviews, participatory observation, and visual documentation across symbolic sites such as the interfaith worship complex, the UNS Museum, and the Javanology Center. The findings reveal that these spaces function as reflective mediums through which academic communities experience nationalism not as rigid doctrine but as a dynamic awareness open to universal values. Four essential components emerged in the construction of the model: symbolic spaces, dialogical narratives, reflective engagement, and institutional support. These findings offer an alternative concept of civic education that is affective, participatory, and contextual, while also demonstrating that the values of Pancasila can serve as a bridge between patriotism and cosmopolitanism within an increasingly transnational higher education landscape